STABLE ISOTOPIC TECHNIQUES TO ADDRESS MARINE POLLUTION: KARACHI COAST AS A CASE STUDY - Mashiatullah, A.; Javed, T.; Chaudhary, M. Z.; Fazil, M.; Khan, M. S.; Ahmad, N.; Qureshi, R. M. (The Nucleus, 2011)
Seawater of the coastal regions near heavily industrialized and thickly populated urbanized centers normally receive large quantities of domestic, agricultural and industrial sewage. Ocean systems generally appear to be unlimited in their ability to dilute these human discharges and industrial wastes. This limit is now being exceeded in coastal waters in the vicinity of many large industrial and heavy populated coastal zones, causing threat to marine coastal resources of these areas. Considering the increasing threats of the unplanned inventory of untreated wastes into the marine coastal environment, the strength of isotope tools (Î´13C) is used to understand the complex ecological systems in the marine coastal environment. This technique has been applied to study transport, behavior and fate of organic pollutants in marine coastal ecosystems of Karachi coast mainly as model studies. Carbon flow in heavily contaminated harbour channel (Manora Channel) , southeast and northwest coast have been investigated. The results indicate that shallow marine coastal waters tend to be depleted in Î´ 13C (TDIC) where polluted rivers through the coastal dwellings enter and get mixed with the seawater. Gradual increase in Î´ 13C (TDIC) are observed as the distance from pollution source is increased. Extremely depleted Î´ 13Corg was observed in sediment of Layari river outfall zone and Karachi fish harbor indicating input of domestic sewage through Layari river. Studies have proved that stable carbon isotope ratios of total dissolved inorganic carbon (TDIC) can be used as an effective tracer of sewage discharge and their transport in shallow marine environment.